Transcatheter Artery Embolization for Postoperative Haemorrhage after Arterio-Venous Malformation – Safer Option - Subrat, Panda; Nalini, Sharma; Aisha, Khan Dina; Anusmita, Saha; Rituparna, Das; Pranjal, Phukan (Acta medica Lituanica, 2021)
Introduction: Hemorrhage is one of the commonest and dreaded complications especially with pelvic surgeries. Gestational trophoblastic neoplasias (GTN) are notorious for their propensity to bleed torrentially and metastasis to vital organs. GTN is associated with an arterio-venous malformation (AVM) about 10-15% of the time, which can lead to bleeding after surgery or after complete remission. After the failure of conventional management with chemotherapy or surgery one is compelled to take another modality of management. One of such methods is the use of transcatheter artery embolization in cases of GTN or post-hysterectomy cases of GTN. Transcatheter artery embolization (TAE) was effective in controlling bleeding due to arterio-venous malformation in 96% of cases.Case: 46 years P2L2A5 (para 2, living issue 2, abortion 5) post-hysterectomy patient presented with bleeding from the vagina after surgery. Twice she underwent vaginal vault repair after hysterectomy but failed. Ultrasonography (USG) showed arterio-venous malformation (AVM); angiography revealed massive extravasation from (left internal iliac artery and abnormal vascularity from the right internal iliac. She was taken up for bilateral internal iliac arteries embolization but again had a heavy bout of bleeding after one week. CT scan confirmed a residual lesion and she underwent a repeat embolization after which the bleeding stopped. Serum BHCG was advised during workup and it was 1997 IU/ml. A diagnosis of GTN was confirmed. The patient was discharged after two cycles of chemotherapy with advice to review for the third one on an outpatient department basis.Conclusion: We concluded that TAE is an effective and safer alternative to surgery in postoperative bleeding from AV malformation in the case of GTN. It can be repeated and should be made to more liberal use in emergency settings.